KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA - Yulisafni Yulisafni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This research is a classroom action research with the aim to improve the learning outcomes of Natural Sciences students in grade VI SD Negeri 019 Bumi Ayu by applying the cooperative learning model numbered heads together (NHT). This research was conducted in two cycles consisting of planning, implementation, observation and reflection. The results of the study showed, in the initial data that was completed as many as 12 students with classical completeness of 48% the category was incomplete. In the first cycle, student learning outcomes have increased with the number of students who completed to 18 students with classical completeness by 72% complete category. In the second cycle, student learning outcomes increased again to 23 students with a classical completeness of 92% complete category. it can be concluded that by implementing numbered heads together (NHT) learning can improve the learning outcomes of students of Class VI of Public Elementary School 019 Bumi Ayu